Myricetin exposure reduces PC differentiation in vitro in primary human B cells - Shabirul Haque; Betty Diamond (Molecular Medicine)
Abstract Background The process of B cell activation and plasma cell (PC) formation involves morphological, transcriptional, and metabolic changes in the B cell. Blocking or reducing PC differentiation is one approach to treat autoimmune diseases that are characterized by the presence of pathogenic autoantibodies. Recent studies have suggested the potential of myricetin, a natural flavonoid with anti-inflammatory and antioxidant properties, to block or reduce PC differentiation. Methods Primary human B cells were purified by using a human B cell isolation kit. B cell subsets such as IgG memory B cells, marginal zone B cells (MZ B cells), and naive B cells were isolated by flow cytometry and activated to induce PC differentiation. Quantification of PCs (CD27 + + , CD38 +) was obtained by flow cytometry. The expression of mRNA was measured by qPCR. Ig secretion in culture supernatant was measured by ELISA. Results Myricetin treatment significantly reduced PC differentiation in primary human B cells and all B cell subsets. Myricetin exposure reduced Ig production both IgM and IgG, in culture supernatants at day 5. Myricetin treatment led to augmented BACH2 expression and reduced IRF4, BLIMP1, and XBP1 expression compared to control cultures. Conclusion Myricetin treatment reduced PC differentiation and Ig secretion by primary human B cells. Targeting B cells in this way may be a therapeutic approach for some autoimmune diseases. Graphical Abstract